ASSESSMENT AND CORELATION OF OXIDATIVE STRESS BETWEEN HEALTHY ADULTS AND ADULT PATIENTS WITH CHRONIC MYELOID LEUKEMIA TREATED WITH IMATINIB - Labachevski, Bojan; Labacevska, Marija Popova; Stavridis, Irina Panovska; Trajkova, Sanja; Veljanovska, Aleksandra Pivkova; Stojanoski, Zlate; Ridova, Nevenka; Zendelovska, Dragica; Petrusevska, Marija; Balkanov, Trajan (Journal of Morphological Sciences; Vol 6 No 1 (2023): JMS, 2023)
Reactive oxygen species (ROS) are oxygen-containing radicals essential for cell signaling and other vital physiological functions. However, their increased production to an excessive amount can cause alterations in the cellular redox status with consecutive disruption of various normal biological functions. Oxidative stress (OS) occurs when there is an imbalance between ROS production and antioxidant defence mechanisms. Chronic OS results in many DNA modifications, and alterations in DNA repair, leading to DNA lesions of which many can be toxic and/or mutagenic. It is proven that OS is involved in the pathogenesis of chronic myeloid leukaemia (CML), a myeloproliferative neoplasm characterized by uncontrolled proliferation of maturing and mature myeloid cells, caused by the presence of translocation t(9;22) leading to the abnormal BCR-ABL fusion protein. Historically treatment options for this disease were limited, with allogeneic stem cell transplant being the only potential curative therapy, but still with poor prognosis. Fortunately, the introduction of tyrosine kinase inhibitors (TKIs) changed dramatically the prognosis of CML patients, turning a once fatal disease, into a chronic and manageable disorder. Analysis of CML patients treated with TKIs revealed a potential correlation between toxic effects of TKIs and levels of ROS. Even though the innovation of this therapy has significantly improved the life expectancy CML patients, still, in some cases, this treatment becomes ineffective. In order to clarify these observations, we measured and correlated the level of oxidative stress between healthy individuals and patients with chronic myeloid leukemia (CML) treated with first generation tyrosine kinase inhibitors (TKIs).The two markers of oxidative stress, d-ROMs and OSI were significantly higher in the group of patients with CML compared to healthy subjects. No statistically significant differences were observed between CML patients and healthy subjects regarding the oxidative stress marker PAT. Keywords : reactive oxygen radicals (ROS), chronic myeloid leukemia (CML), oxidative stress (OS), imatinib, d-ROMs, PAT, OSI. https://doi.org/10.55302/JMS2361051l